Organoid Bioengineering Advances, Applications and Challenges - Paul, Manash K. (Biomedical Engineering, 2022)
Organoids are three-dimensional miniature tissue mimics established from embryonic stem cells, human pluripotent stem cells, adult stem cells, and cancer cells. These fascinating 3D organoids serve as a valuable tool for fundamental research, disease modeling, drug screening and discovery, regenerative medicine, and deciphering the mechanism of disease pathogenesis. This book emphasizes the emerging data and critical resources covering the fundamentals of organoids and their use in modeling and application in various diseases, especially cancer. The chapters deal with organoid bioengineering in cerebral organoids, retinal organoids, tumoroids, and organoid commercialization. This book is intended for a broad readership and is an indispensable resource for basic biologists, translational scientists, and clinicians.